Subaltern Women, State Neglect, and Climate Precarity: Rethinking Forest Landscape Governance in Indonesia - Hendrastiti, Titiek Kartika; Kusujiarti, Siti (The Indonesian Journal of Socio-Legal Studies, 2026)
This article examines the social positioning and struggles of subaltern women in East Java, Indonesia, within the intersecting conditions of state neglect and climate precarity in Forest Landscape Governance (FLG). Drawing on field research conducted between 2022 and 2023, it employs Postcolonial Feminist Political Ecology (PFPE) and Postcolonial Feminist Participatory Action Research (PFPAR) to analyze how governance regimes simultaneously depend upon yet marginalize women’s ecological labor. Based on field conversations, storytelling, focus group discussions, participatory drawing, and community dialogues in Banyuwangi and Trenggalek, the study shows that subaltern women remain largely invisible within formal governance frameworks, despite their central role in sustaining environmental and household resilience. This exclusion is not incidental but structurally embedded in bureaucratic, legal, and policy mechanisms that fail to recognize informal ecological labor and gendered knowledge systems. By foregrounding subaltern women’s narratives, the article advances a postcolonial feminist critique of FLG, demonstrating how governance frameworks reproduce colonial and gendered hierarchies through epistemic marginalization and bureaucratic exclusion. It argues that achieving inclusive and just forest governance requires not only institutional reform but also epistemic recognition of marginalized women’s knowledge, agency, and environmental stewardship. The article contributes to socio-legal debates on governance, climate justice, and the decolonization of environmental policy in Indonesia.